2016
DOI: 10.1103/physrevd.93.045004
|View full text |Cite
|
Sign up to set email alerts
|

Sterile neutrinos with pseudoscalar self-interactions and cosmology

Abstract: Sterile neutrinos in the electronvolt mass range are hinted at by a number of terrestrial neutrino experiments. However, such neutrinos are highly incompatible with data from the Cosmic Microwave Background and large scale structure. This paper discusses how charging sterile neutrinos under a new pseudoscalar interaction can reconcile eV sterile neutrinos with terrestrial neutrino data. We show that this model can reconcile eV sterile neutrinos in cosmology, providing a fit to all available data which is way b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 52 publications
3
66
1
Order By: Relevance
“…The scenario of [45,243,250] assumes instead a non-standard interaction between the mainly sterile mass state ν 4 and a pseudoscalar field in a dark sector with a mass m φ m 4 . Assuming a pseudoscalar rather than a scalar boson allows to evade fifth force bounds.…”
Section: Avenues For Reconciling Light Sterile Neutrinos With Cosmologymentioning
confidence: 99%
“…The scenario of [45,243,250] assumes instead a non-standard interaction between the mainly sterile mass state ν 4 and a pseudoscalar field in a dark sector with a mass m φ m 4 . Assuming a pseudoscalar rather than a scalar boson allows to evade fifth force bounds.…”
Section: Avenues For Reconciling Light Sterile Neutrinos With Cosmologymentioning
confidence: 99%
“…So, to avoid large non-minimal coupling, and for simplicity we shun the Higgs as inflaton. Using χ as inflaton is also problematic, as to have enough energy flow to the Higgs sector (and thus to SM sector) we need the field χ to couple to the Higgs field, but that consequently leads to a mass term of the χ field, thus χ not being light enough to evade Σm ν bound [44]. In order to bypass the above issues related to Higgs and χ fields, we introduce a separate inflaton field φ.…”
Section: Inflation Quantum Corrections and Threat To Flatness Of Potmentioning
confidence: 99%
“…2 While within the paradigm of standard cosmology all these constraints impact on the viability of a light sterile neutrino with sizable active-sterile mixing, it has been shown that the CMB constraints can be partly relaxed going beyond the standard cosmology modifying the primordial power spectrum at small scales [37], within the paradigm of modified gravity [38], within BSM physics with time-varying Dark Energy component [39], by light dark matter [40], from large lepton asymmetry [41]. However, it has been also pointed out that additional interactions in the sterile neutrino sector can also render such a scenario viable [42][43][44][45]. The presence of such interaction leads to the suppression of the active-sterile mixing angle and thus delay the DW production.…”
mentioning
confidence: 99%
“…[28] and have similar origin, namely, the initial velocity perturbations derived from a previous acoustic phase. These features are distinct from those of the other nonstandard models for which the growth of perturbations has been studied in detail [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The purpose of this paper is to introduce this BDM model, highlight its predictions, and explain them analytically.…”
Section: Introductionmentioning
confidence: 96%